2020
DOI: 10.1002/anie.202008175
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Protein Corona Composition and Dynamics on Carbon Nanotubes in Biological Environments

Abstract: When nanoparticles enter biological environments, proteins adsorb to form the “protein corona” which alters nanoparticle biodistribution and toxicity. Herein, we measure protein corona formation on DNA‐functionalized single‐walled carbon nanotubes (ssDNA‐SWCNTs), a nanoparticle used widely for sensing and delivery, in blood plasma and cerebrospinal fluid. We characterize corona composition by mass spectrometry, revealing high‐abundance corona proteins involved in lipid binding, complement activation, and coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 64 publications
(144 reference statements)
2
92
0
Order By: Relevance
“…When GFP DNA was mixed with unfunctionalized SWCNTs in solution, a moderate increase in fluorescence was observed, suggesting that electronic coupling was occurring between the two moieties. This is likely due to a protein corona, where proteins may electrostatically interact with the SWCNTs, leading to changes in the optical properties in SWCNT/GFPDNA mixtures [41][42][43]. When GFPDNA was directly coupled to SWCNTs via complementary DNA, a significant, and much larger, increase in emission intensity of the GFP occurred, suggesting a stronger electronic coupling between the SWCNT and GFP.…”
Section: Optical Characterization Of Swcnt-gfp Hybrids In Solutionmentioning
confidence: 99%
“…When GFP DNA was mixed with unfunctionalized SWCNTs in solution, a moderate increase in fluorescence was observed, suggesting that electronic coupling was occurring between the two moieties. This is likely due to a protein corona, where proteins may electrostatically interact with the SWCNTs, leading to changes in the optical properties in SWCNT/GFPDNA mixtures [41][42][43]. When GFPDNA was directly coupled to SWCNTs via complementary DNA, a significant, and much larger, increase in emission intensity of the GFP occurred, suggesting a stronger electronic coupling between the SWCNT and GFP.…”
Section: Optical Characterization Of Swcnt-gfp Hybrids In Solutionmentioning
confidence: 99%
“…To understand the impact of different covalently linked polymers on protein adsorption to the SWNT surface, we performed an assay to test the adsorption of fibrinogen, a protein known to be highly involved in the formation of nanoparticle coronas. [32] We have previously demonstrated that the fluorescence of FAM-labeled fibrinogen (FAM-FBG) is quenched when this species adsorbs to a SWNT surface. [33] Therefore, we can use this solution-phase and real-time ligand binding assay to quantify the amount of protein that adsorbs onto a nanoparticle surface.…”
Section: Resultsmentioning
confidence: 99%
“…The ssDNA sequence of (GT) 6 was chosen based on high SWCNT suspension yield. The short ssDNA sequence length (12 nucleotides) was informed by previous work demonstrating that shorter ssDNA desorbs faster, and to a greater extent, from SWCNTs in the presence of proteins ( 33, 34 ). (GT) 6 -SWCNTs (2.5 mg/L final concentration) were incubated with ACE2 sensing protein (6.25 mg/L final concentration) in 0.1 M phosphate-buffered saline (PBS) solution to noncovalently passivate the SWCNT surface with protein, schematically represented in Figure 1A ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…The short ssDNA sequence length (12 nucleotides) was informed by previous work demonstrating that shorter ssDNA desorbs faster, and to a greater extent, from SWCNTs in the presence of proteins ( 33, 34 ). (GT) 6 -SWCNTs (2.5 mg/L final concentration) were incubated with ACE2 sensing protein (6.25 mg/L final concentration) in 0.1 M phosphate-buffered saline (PBS) solution to noncovalently passivate the SWCNT surface with protein, schematically represented in Figure 1A ( 34 ). This ratio of ACE2 sensing protein to SWCNT substrate was calculated to be approximately above the close-packing threshold to minimize protein surface-denaturation and colloidal aggregation, then this calculated value was experimentally optimized (see details in SI and Figure S1, Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%